Physical, cognitive, and psychosocial conditions in relation to anticoagulation satisfaction among elderly adults with atrial fibrillation: The SAGE‐AF study. (25th September 2019) - Wang, Weijia; Saczynski, Jane; Lessard, Darleen; Mailhot, Tanya; Barton, Bruce; Waring, Molly E.; Sogade, Felix; Hayward, Robert; Helm, Robert; McManus, David D.
Abstract: Background: Successful anticoagulation is critical for stroke prevention in adults with atrial fibrillation (AF). Anticoagulation satisfaction is a key indicator of treatment success. While physical, cognitive, and psychosocial limitations are common in elderly AF patients, their associations with anticoagulation satisfaction are unknown. Objective: Examine whether anticoagulation satisfaction differs among AF patients with and without physical, cognitive, and psychosocial conditions. Methods: The study comprised AF patients greater than or equal to 65 years old who were prescribed an oral anticoagulant (warfarin 57%; direct oral anticoagulant [DOAC] 43%). Frailty, cognitive function, social support, depressive symptoms, vision, hearing, and anxiety were assessed using validated measures. Anticoagulation satisfaction was measured using the anticlot treatment scale. Results: Participants ( n  = 1037, 50% female) were on average 76 years old. The following conditions were prevalent: frailty (14%), cognitive impairment (42%), social isolation (13%), vision impairment (35%), hearing impairment (36%), depression (29%), and anxiety (24%). Average anticlot treatment burden scale was 55 out of 60 (lower burden scales indicating higher perceived burden). Patients with high perceived burden were older, more likely to be female, and receive warfarin. After adjusting for confounders, visual impairment (adjusted odds ratio [95% confidence interval]: 1.7 [1.2‐2.4]), depressive symptoms (2.4 [1.6‐3.7]), and anxiety (1.8 [1.2‐2.7]) were significantly associated with high perceived burden. Different conditions were associated with high perceived burden in warfarin vs DOAC users. Conclusion: Physical, cognitive, and psychosocial limitations are prevalent and associated with high perceived anticoagulation burden among elderly AF adults. These conditions merit consideration in anticoagulation prescribing.